Temperature trends of the permittivity in complex oxides of rare-earth elements with perovskite-type structure - Belous, A.G.; Ovchar, O.V.; Mischuk, D.O. (Condensed Matter Physics, 2003)
Ceramic materials based on complex oxides with both the perovskite structure (Ln₂/₃Nb₂O₆) and the structure of tetragonal tungsten bronze (Ba₆−xLn₈+₂x/₃Ti₁₈O₅₄) have been investigated over a wide frequency and temperature ranges. The results obtained for certain structures denote the presence of the temperature anomalies of dielectric parameters (є, tan δ). These anomalies occur over the wide frequency range including submilimeter (SMM) wavelength range, and are related neither with the processing peculiarities nor with the presence of the phase transitions. Temperature behavior of the permittivity has been considered in terms of the polarization mechanism based on the elastic-strain lattice oscillations. It has been assumed that the observed anomalies could be ascribed to a superposition of harmonic and anharmonic contribution to lattice oscillations that determines τe sign and magnitude.